Endoscopic ultrasound (EUS) and the management of pancreatic cancer. Issue 1 (14th May 2020) - Yousaf, Muhammad Nadeem; Chaudhary, Fizah S; Ehsan, Amrat; Suarez, Alejandro L; Muniraj, Thiruvengadam; Jamidar, Priya; Aslanian, Harry R; Farrell, James J
Abstract : Pancreatic cancer is one of the leading causes of cancer-related mortality in western countries. Early diagnosis of pancreatic cancers plays a key role in the management by identification of patients who are surgical candidates. The advancement in the radiological imaging and interventional endoscopy (including endoscopic ultrasound (EUS), endoscopic retrograde cholangiopancreatography and endoscopic enteral stenting techniques) has a significant impact in the diagnostic evaluation, staging and treatment of pancreatic cancer. The multidisciplinary involvement of radiology, gastroenterology, medical oncology and surgical oncology is central to the management of patients with pancreatic cancers. This review aims to highlight the diagnostic and therapeutic role of EUS in the management of patients with pancreatic malignancy, especially pancreatic ductal adenocarcinoma.